Combining refutations and social norms increases belief change. Issue 6 (June 2023) - Ecker, Ullrich KH; Sanderson, Jasmyne A; McIlhiney, Paul; Rowsell, Jessica J; Quekett, Hayley L; Brown, Gordon DA; Lewandowsky, Stephan
Misinformed beliefs are difficult to change. Refutations that target false claims typically reduce false beliefs, but tend to be only partially effective. In this study, a social norming approach was explored to test whether provision of peer norms could provide an alternative or complementary approach to refutation. Three experiments investigated whether a descriptive norm—by itself or in combination with a refutation—could reduce the endorsement of worldview-congruent claims. Experiment 1 found that using a single-point estimate to communicate a norm affected belief but had less impact than a refutation. Experiment 2 used a verbally presented distribution of four values to communicate a norm, which was largely ineffective. Experiment 3 used a graphically presented social norm with 25 values, which was found to be as effective at reducing claim belief as a refutation, with the combination of both interventions being most impactful. These results provide a proof of concept that normative information can aid in the debunking of false or equivocal claims, and suggests that theories of misinformation processing should take social factors into account.